Lianas and trees 30-years after liana cutting and selective logging in the Amazon - Vitoria Duarte Derisso; Maria Tereza Grombone-Guaratini; Francis E. Putz; Rodrigo Costa Pinto; Iran Paz Pires; Edson Vidal (Forest Ecology and Management, 2026)

Reduced-impact logging shortens carbon recovery time in eastern Amazonian forests - Nathalia Sousa Braga; Jonathan William Trautenmüller; Edson Vidal (Journal of Environmental Management, 2026)

The recovery of forest structure 30 years after timber harvesting: a comparison of harvesting methods using field inventories and drone-based LiDAR data - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2026)

Impact of different management practices on tree biomass and carbon dynamics 30 years after logging in eastern Amazon - Edson Vidal; Nathalia Sousa Braga; Daigard Ricardo Ortega Rodriguez; Vitoria Duarte Derisso; Rodrigo Costa Pinto; Jéssy Anni Vilhena Senado; Jonathan William Trautenmüller (Journal of Environmental Management, 2026)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Natural regeneration responses of tree species at the end of the first timber harvesting cycle in the Eastern Amazon - Rodrigo Costa Pinto; Eric Bastos Gorgens; Danilo Roberti Alves de Almeida; Marielos Peña-Claros; Gustavo Schwartz; Edson Vidal (Forest Ecology and Management, 2025)

Management intensity does not affect the ecological indicators of coffee agroforestry systems in agricultural landscapes of the Atlantic forest zone in Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Catherine Torres de Almeida; Pedro H. S. Brancalion; Danilo R. A. Almeida; Paulo G. Molin; Aline Souza; Edson Vidal (Agroforestry Systems, 2025)

Maintaining genetic diversity in the Amazon: Species-specific strategies are more effective for managed forests than generalist criteria in Brazilian legislation - Vanessa Erler Sontag; Beatriz Dadio; Guilherme Bovi Ambrosano; Samira Rodrigues Miguel; Daigard Ricardo Ortega Rodriguez; Cláudia Fontana; Gabriel Assis-Pereira; Edson Vidal (Forest Ecology and Management, 2025)

Ecological indicators for monitoring coffee agroforestry systems in protected areas: A case study in São Paulo State, Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Ricardo Augusto Gorne Viani; Haroldo Borges Gomes; Edson Vidal (Agricultural Systems, 2025)

Gene flow, mating patterns and inbreeding depression in Roupala montana var. brasiliensis, a neotropical timber species - Fernanda B. Pereira; Alexandre M. Sebbenn; David H. Boshier; Bruno C. Rossini; Celso L. Marino; Miguel L. M. Freitas; João R. B. F. Rosa; Edson Vidal; Evandro V. Tambarussi (New Forests, 2024)

Magnetic graphene derivates for efficient herbicide removal from aqueous solution through adsorption - Theodoro da Rosa Salles; Leonardo Vidal Zancanaro; Franciele da Silva Bruckmann; Wagner Jesus Garcia; Artur Harres de Oliveira; Luiza Baumann; Daniele Soares Basso Rhoden; Edson Irineu Muller; Diego Stefani Teodoro Martinez; Sergio Roberto Mortari; Cristiano Rodrigo Bohn Rhoden (Environmental Science and Pollution Research, 2024)

Physiological responses of tomato plants subjected to various combinations of irrigation levels with mineral and organomineral sources of phosphorus - Oswaldo Palma Lopes Sobrinho; Leonardo Nazário Silva dos Santos; Adinan Alves da Silva; Frederico Antônio Loureiro Soares; Fernando Nobre Cunha; Vitor Marques Vidal; Marconi Batista Teixeira; Edson Cabral da Silva; Nelmício Furtado da Silva; Alan Carlos da Costa (Acta Physiologiae Plantarum, 2022)

Industrial Quality of Sugarcane Under Fertigation with Nitrogen and Zinc - Fernando Nobre Cunha; Marconi Batista Teixeira; Frederico Antonio Loureiro Soares; Edson Cabral da Silva; Antonio Evami Cavalcante Sousa; Leonardo Nazário Silva dos Santos; Nelmício Furtado da Silva; Wilker Alves Morais; Vitor Marques Vidal; Fernando Rodrigues Cabral Filho; Gustavo da Silva Vieira (Sugar Tech, 2020)

Giardia spp. and Cryptosporidium spp. removal efficiency of a combined fixed-film system treating domestic wastewater receiving hospital effluent - Sandra Yamashiro; Mário Luiz Rodrigues Foco; Carolina Ortiz Pineda; Juliana José; Edson Aparecido Abdul Nour; Isabel Cristina Vidal Siqueira-Castro; Regina Maura Bueno Franco (Environmental Science and Pollution Research, 2019)

Effects of stretching on morphological and biochemical aspects of the extracellular matrix of the rat calcaneal tendon - Fernanda Martins de Almeida; Tatiana Carla Tomiosso; Adriano Biancalana; Stela Marcia Mattiello-Rosa; Benedicto Campos Vidal; Laurecir Gomes; Edson Rosa Pimentel (Cell and Tissue Research, 2010)

Quantitative detection of Citrus tristeza virus in plant tissues and single aphids by real-time RT-PCR - Edson Bertolini; Aranzazu Moreno; Nieves Capote; Antonio Olmos; Ana de Luis; Eduardo Vidal; Jordi Pérez-Panadés; Mariano Cambra (European Journal of Plant Pathology, 2008)

Extracellular Matrix of Porcine Pericardium: Biochemistry and Collagen Architecture - Antonella Sachsida Braga-Vilela; Edson Rosa Pimentel; Sergio Marangoni; Marcos Hikari Toyama; Benedicto de Campos Vidal (The Journal of Membrane Biology, 2008)

Beyond Reaping the First Harvest: Management Objectives for Timber Production in the Brazilian Amazon - DANIEL J. ZARIN; MARK D. SCHULZE; EDSON VIDAL; MARCO LENTINI (Conservation Biology, 2007)
Millions of hectares of future timber concessions are slated to be implemented within large public forests under the forest law passed in 2006 by the Brazilian Congress. Additional millions of hectares of large, privately owned forests and smaller areas of community forests are certified as well managed by the Forest Stewardship Council, based on certification standards that will be reviewed in 2007. Forest size and ownership are two key factors that influence management objectives and the capacity of forest managers to achieve them. Current best ecological practices for timber production from Brazil's native Amazon forests are limited to reduced‐impact logging (RIL) systems that minimize the environmental impacts of harvest operations and that obey legal restrictions regarding minimum diameters, rare species, retention of seed trees, maximum logging intensity, preservation of riparian buffers, fire protection, and wildlife conservation. Compared with conventional, predatory harvesting that constitutes >90% of the region's timber production, RIL dramatically reduces logging damage and helps maintain forest cover and the presence of rare tree species, but current RIL guidelines do not assure that the volume of timber removed can be sustained in future harvests. We believe it is counterproductive to expect smallholders to subscribe to additional harvest limitations beyond RIL, that larger private forested landholdings managed for timber production should be sustainable with respect to the total volume of timber harvested per unit area per cutting cycle, and that large public forests should sustain volume production of individual harvested species. These additional requirements would improve the ecological sustainability of forest management and help create a stable forest‐based sector of the region's economy, but would involve costs associated with lengthened cutting cycles, reduced harvest intensities, and/or postharvest silviculture to promote adequate growth and regeneration.

Changes in Liana Abundance and Species Diversity Eight Years after Liana Cutting and Logging in an Eastern Amazonian Forest - Jeffrey J. Gerwing; Edson Vidal (Conservation Biology, 2002)
Lianas are characteristic of many tropical forests and may serve multiple ecosystem functions. They can also increase logging damage and slow tree growth. Liana cutting prior to logging is a silvicultural tool used to mitigate these negative effects. We assessed the effects of complete liana cutting followed by reduced‐impact logging on liana abundance and species diversity. Eight years following liana cutting and 6 years following logging there was a 55% reduction in the stem density of climbing lianas ≥1 cm diameter in size. Liana basal area, aboveground biomass, and leaf area index decreased by approximately 85%. Coppicing of cut stems was the primary mode of liana recruitment. Liana cutting and logging resulted in a 14% reduction in the number of liana species present in a 0.20‐ha sample, but a cumulative species‐area curve suggested that this percentage might have been reduced if a larger area were sampled. Our results suggest that the silvicultural benefits of complete liana cutting—reduced logging damage and increased postlogging tree growth—need to be weighed against the costs of reduced species diversity of lianas and the possible effects on forest ecosystem functioning (e.g., reduced fruit and flower availability) that are likely to persist long after initial liana cutting.